Wire Melt Electrospinning of Thin Polymeric Fibers via Strong Electrostatic Field Gradients. Issue 1 (2nd November 2018) - Morikawa, Kai; Vashisth, Aniruddh; Grimme, Christian J.; Green, Micah J.; Naraghi, Mohammad
Abstract: Here, a novel melt electrospinning method to produce few‐micron and nanometer thick fibers is presented, in which a polymer‐coated wire with a sharp tip is used as the polymer source. The polymer coating is melted via Joule heating of the source wire and extracted toward the target via electrostatic forces. The high viscosity and low charge density of polymer melts lower their stretchability in melt. The method relies on confining the Taylor cone and reducing initial jet diameter via concentrated electrostatic fields as a means to reduce the diameter of fibers. As a result, the initial jet diameter and the final fiber diameter are reduced by an order of magnitude of three to ten times, respectively, using wire melt electrospinning compared to syringe‐ and edge‐based electrospinning. The fiber diameter melt electrospun via this novel method is 1.0 ± 0.9 µm, considerably thinner than conventional melt electrospinning techniques. The generation of thin fibers are explained in terms of the electrostatic field around the wire tip, as obtained from finite element analysis (FEA), which controls the size and shape of the melt electrospun jet. Abstract : A novel melt electrospinning approach to produce few‐micron and sub‐micron thick fibers from polymer melt is presented. The method relies on confining the Taylor cone and electrospinning jet via concentrated electrostatic fields as a means to reduce the diameter of fibers. The fiber diameter spun via this novel method is 1.0 ± 0.9 µm, considerably thinner than conventional melt electrospinning techniques.